Paid basic income, fertility rates and economic growth - Elise S. Brezis (Bar-Ilan University, Department of Economics, 2014)
The purpose of this paper is to examine the effects of paid basic income on fertility rates in a model in which fertility rates are endogenous. I show that when child labor is not a crucial part of the income of the family, then paid basic income will lead to higher fertility rates. However, when child labor is a necessity, then in fact an increase in paid basic income will lead to a reduction in fertility rates.
Keywords: B10; D10; J13; 330; basic income; fertility rates; economic growth; child labor; Sibship size effect